Optimization of Raw Material Inventory Control Using Linear Programming Method at CV Sidomulyo in Palu City - Sucipto, Mohammad Adhi; Syamsuddin, Syamsuddin; Miru, Sulaeman; Hadi, Suryadi (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
This study aims to optimize raw material inventory control and reduce cost waste at CV Sidomulyo using the linear programming method assisted by POM-QM for Windows software. The data used consists of primary data in the form of inventory quantities and raw material prices and secondary data from company documents. The linear programming method was chosen because it is able to provide an optimal solution in allocating limited resources by considering various existing constraints, making it suitable for inventory efficiency problems. The results of the analysis show that the optimal annual procurement quantities are 150 liters of paint, 20 kg of nails, 24 pcs of glue, and 2,480 sheets of wood or 24.80 m³. The application of this method resulted in cost savings of Rp68,814,500 compared to the previous cost. Theoretically, this research strengthens the application of efficiency and optimization concepts in operations management through a quantitative approach, and proves that linear programming can be used as a strategic tool in inventory decision making. The limitation of this study lies in the scope of data that only covers one production period and has not considered price fluctuations or seasonal demand. The findings are expected to be the basis for further research and practical reference in more efficient inventory management.